2016
DOI: 10.5194/isprs-archives-xli-b5-821-2016
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Underwater Photogrammetric Three Dimensional Modelling for Coral Reefs

Abstract: ABSTRACT:Recent advances in automation of photogrammetric 3D modelling software packages have stimulated interest in reconstructing highly accurate 3D object geometry in unconventional environments such as underwater utilizing simple and low-cost camera systems. The accuracy of underwater 3D modelling is affected by more parameters than in single media cases. This study is part of a larger project on 3D measurements of temporal change of coral cover in tropical waters. It compares the accuracies of 3D point cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…A further degradation by approximately a factor two can be considered for underwater photogrammetry (Maas, 2015), leading to a final theoretical accuracy of about 1.6 mm, which is still an order of magnitude better than the accuracy provided by the underwater geodetic network (short poles). Also this theoretical value correlates well with a past empirical analysis performed with the same camera system (Guo et al, 2016).…”
Section: Photogrammetric Accuracysupporting
confidence: 88%
“…A further degradation by approximately a factor two can be considered for underwater photogrammetry (Maas, 2015), leading to a final theoretical accuracy of about 1.6 mm, which is still an order of magnitude better than the accuracy provided by the underwater geodetic network (short poles). Also this theoretical value correlates well with a past empirical analysis performed with the same camera system (Guo et al, 2016).…”
Section: Photogrammetric Accuracysupporting
confidence: 88%
“…Our lower accuracy was to be expected, as we did not calibrate cameras and used a considerably less time-consuming rendering process compared to other methods: e.g., methods that include manually removing outlier points on 3D models, manually identifying ground control objects, and/or using PhotoScan’s high or ultra-high quality settings. [55] showed that models from calibrated GoPro footage can achieve RMSE errors of 0.40 mm; users requiring models accurate at scales finer than 1.5 cm should consider a method requiring higher hardware/software effort and cost or at minimum calibrate their cameras.…”
Section: Resultsmentioning
confidence: 99%
“…Two different types of underwater cameras are evaluated in a preliminary study of accuracy for the monitoring of coral reefs (Guo et al 2016). In-air and underwater calibrations were undertaken, validated by an accurately known target fixture and 3D point cloud models of cinder blocks.…”
Section: Validation Resultsmentioning
confidence: 99%